Preparation method and application of semi-coke-based high-rate long-life hard carbon material
By adding sodium carbonate and zinc phosphate to orchid carbon and calcining treatment, orchid carbon-based hard carbon materials were prepared, which solved the complex problem of coal tar and gas treatment during coal pyrolysis, and achieved efficient and low-cost hard carbon materials preparation, with excellent electrochemical performance and industrial potential.
Patent Information
- Application Number
- CN202411995439.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
When using coal directly to prepare hard carbon materials, the post-processing of coal tar and gas generated during the pyrolysis process is complicated, resulting in a significant increase in material costs.
By adding sodium carbonate and zinc phosphate to orchid and calcining under an inert atmosphere, a hard carbon-based material was prepared, which improved the first-circle coulomb efficiency, rate performance and long cycle life of the material.
It realizes the high specific surface area, stable structure and excellent electrochemical properties of the orchid-based hard carbon material, reduces production costs and is suitable for industrial applications.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a blue charcoal-based high-rate and long-life hard carbon material, belonging to the technical field of sodium ion batteries. Background Art
[0002] Lithium-ion batteries are currently the main technology for large-scale electrochemical energy storage, but the scarcity of lithium resources and the safety of lithium batteries limit its further development. Sodium has the advantages of abundant reserves, wide distribution and low price. It can solve the problems of high price and limited resources of lithium-ion batteries, and is expected to become a widely used energy storage device after lithium-ion batteries. Drawing on the research experience of lithium-ion batteries, the research on sodium-ion batteries has developed rapidly. However, due to the thermodynamic instability of the compounds formed between sodium ions and graphite, graphite, the negative electrode material of commercial lithium-ion batteries, cannot be directly applied to sodium-ion batteries. It is crucial to find a suitable negative electrode material for sodium storage.
[0003] As an important component of sodium-ion batteries, the battery negative electrode determines the capacity and voltage of the battery. Carbon negative electrode materials represented by hard carbon are one of the main research directions. At present, hard carbon is mainly made from biomass, high molecular polymers, etc. by high-temperature carbonization. Hard carbon has a disordered, stacked microcrystalline structure that presents abundant sodium storage sites and a loose and suitable ion storage and transportation environment, and has high capacity and rate capability. The microcrystalline structure of carbon materials is one of the key factors that determine electrochemical performance. The short-range, loose microcrystalline structure is conducive to improving the sodium storage environment. Developing an effective microcrystalline structure-oriented regulation strategy is of great significance for the development of carbon negative electrode materials for sodium-ion batteries.
[0004] It is an important development direction to develop low-cost, high-performance sodium ion electrode materials using natural high-carbon abundance and high-reserve coal as raw materials. China is the largest carbon-based negative electrode material market in Asia, and northern Shaanxi is one of the main sources of high-quality coal resources in my country. Developing high-quality coal into hard carbon materials will help energy transformation and increase the added value of coal.
[0005] At present, there are a number of Chinese patent applications involving the preparation of hard carbon materials using coal (anthracite, lignite, etc.) as raw materials, such as: a coal-based hard carbon negative electrode sodium storage material and its preparation method and application 202411348617.2, a coal-based hard carbon negative electrode sodium storage material and its preparation method and application 202411348617.2, a lignite-based power / capacity type sodium ion battery hard carbon negative electrode flexible control method and application 202310561066.7, a sodium ion battery coal-based hard carbon negative electrode material and its preparation method 202410068438.7, a nitrogen-doped coal-based hard carbon material and its preparation method and application, secondary battery 202310485334.1, etc. The most prominent problem in directly using coal to prepare hard carbon materials is that coal produces a large amount of coal tar and coal gas during the pyrolysis process. The subsequent treatment of coal tar and coal gas is complicated, resulting in the subsequent investment in coal tar and coal gas treatment will be far greater than the initial investment in equipment for pyrolysis to make hard carbon, causing the cost of the final material to rise sharply. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method and application of a blue charcoal-based hard carbon material. The first-cycle coulomb efficiency, rate performance and long cycle life of the hard carbon material are improved by adding sodium carbonate and doping with heteroatoms. The raw materials of the present invention are easily available and low in cost. The preparation process is simple, the pollution is small, the carbon yield is high, and it is suitable for industrialization.
[0007] To achieve the above objectives, the present invention provides the following technical solutions.
[0008] A method for preparing a blue charcoal-based hard carbon material comprises the following steps: (1) crushing and sieving the semi-coke to obtain semi-coke fine powder; (2) The semi-coke fine powder is acid-washed to remove impurities, then washed with water until neutral, and dried to obtain acid-washed semi-coke; (3) Evenly mixing the acid-washed semi-coke with sodium carbonate and zinc phosphate, wherein the mass ratio of semi-coke, sodium carbonate and zinc phosphate is 10:(0.3-2):(0.3-2); (4) The blend obtained in step (3) is calcined at 1000-1500° C. under an inert atmosphere to obtain a blue charcoal-based hard carbon material.
[0009] In the above step (1), the semi-coke is crushed and passed through a 200-mesh sieve to obtain semi-coke fine powder.
[0010] In the above step (2), pickling uses one or more mixed acids selected from hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, propionic acid, and ethylenediaminetetraacetic acid, and the acid concentration is 0.5-6 mol / L.
[0011] In the above step (3), the mass ratio of blue carbon, sodium carbonate and zinc phosphate is 10: (0.5-1.5): (0.5-1.5).
[0012] In the above step (3), the blending is carried out by ball milling, mechanical stirring or rotary stirring.
[0013] In the above step (4), the inert atmosphere protective gas is a mixture of one or more of nitrogen, argon and carbon dioxide.
[0014] In the above step (4), the calcination is carried out in stages, room temperature - (550-650°C) - (800-950°C) - (1000-1500°C), and each stage is kept warm for 20 minutes to 2 hours.
[0015] In the above step (4), the calcined blue charcoal-based hard carbon material is subjected to acid washing and drying treatment.
[0016] The blue charcoal-based hard carbon material prepared by the preparation method provided by the present invention has a larger (002) crystal plane interlayer spacing, a smaller specific surface area and a lower degree of graphitization. The sodium ion battery made of the hard carbon material prepared by the preparation method of the present invention has a higher reversible capacity and excellent cycle stability. The specific surface area of the prepared hard carbon material is 2~23m 2 g -1 The interlayer spacing of the hard carbon material is 0.37-0.41 nm; the degree of graphitization ID / IG is 1.20-1.26. The present invention is more conducive to the application of the material in the negative electrode of sodium ion battery through process condition regulation and optimization, and obtains better battery rate performance and long cycle stability.
[0017] The outstanding advantages of the present invention are: (1) blue charcoal is selected as the raw material for preparing hard carbon. Blue charcoal is made by burning clean coal blocks, and is mainly low-temperature carbonization, and the carbonization temperature is generally around 600°C. As a new type of carbon material, it has the characteristics of high fixed carbon, high specific resistivity, high chemical activity, low ash content, low aluminum, low sulfur, and low phosphorus; (2) Blue charcoal has the characteristics of low cost, high carbon content, low volatile component content, and low environmental pollution; (3) The present invention uses green and environmentally friendly anhydrous sodium carbonate as a further impurity remover and pore-forming agent, so that the impurity content in blue charcoal is reduced and the specific surface area of the prepared hard carbon material is slightly increased, providing more sodium ion active sites and improving sodium storage performance; (4) The present invention uses heteroatom doping (P, Zn) to make the obtained hard carbon material have a more stable structure, with the characteristics of high first coulomb efficiency, high rate performance and excellent long cycle performance. Further, through process optimization, the sodium ion battery prepared by the negative electrode material has better stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM image of the blue charcoal-based hard carbon material prepared in Example 1 of the present invention; Figure 2 This is the BET adsorption curve of the blue charcoal-based hard carbon material prepared in Example 1 of the present invention; Figure 3 This is the XRD pattern of the blue charcoal-based hard carbon material prepared in Example 1 of the present invention; Figure 4 TEM image of the blue charcoal-based hard carbon material prepared in Example 1 of the present invention; Figure 5 The Raman spectra of the blue charcoal-based hard carbon materials prepared in Examples 1 to 4 of the present invention; Figure 6 This is the first charge and discharge diagram of the blue charcoal-based hard carbon material prepared in Example 1 of the present invention; Figure 7 This is a rate performance diagram of the blue charcoal-based hard carbon material prepared in Example 1 of the present invention; Figure 8 This is a long cycle performance diagram of the blue charcoal-based hard carbon material prepared in Example 1 of the present invention; Fig. 9 This is the XRD pattern of the blue charcoal-based hard carbon material prepared in Comparative Example 1 of the present invention; Fig.10 This is the first charge and discharge diagram of the blue charcoal-based hard carbon material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0019] The technical solution and effects of the present invention are further described below in conjunction with specific implementations. The following implementations are only used to illustrate the content of the present invention, but cannot be used to limit the scope of the present invention. Example
[0020] A method for preparing a blue carbon-based hard carbon negative electrode material, the preparation steps are as follows: (1) crushing the raw semi-coke, grinding it and then screening it to obtain 200-mesh coal powder; (2) The pulverized coal obtained in step (1) is pickled with 2 mol / L hydrochloric acid for 12 h, then washed with water until neutral, and dried to obtain acid-washed blue carbon; (3) 10 g of the acid-washed semi-carbonate obtained in step (2) was mixed with 1 g of anhydrous sodium carbonate and 1 g of zinc phosphate tetrahydrate, and then ball milled for 2 h, with a ball-to-mass ratio of 3:1 and a rotation speed of 300 r / min; (4) The mixture obtained in step (3) was placed in a square alumina crucible and heated to 650°C at a rate of 5°C / min under an argon atmosphere. ℃; then increase the temperature to 950℃ at a rate of 1℃ / min and keep it at that temperature for 0.5h; then increase the temperature to 1300℃ at a rate of 5℃ / min ℃ and keep warm for 2h, then cool naturally to room temperature.
[0021] (5) The blue charcoal-based hard carbon material obtained in step (4) is pickled with 2 mol / L hydrochloric acid, then washed with water until neutral and dried to obtain a blue charcoal-based hard carbon material that is ultimately used as a negative electrode material for a sodium ion battery.
[0022] The conditions for preparing button half-cells for sodium metal using the prepared hard carbon material are as follows: slurry ratio, hard carbon: Super-p: CMC = 8:1:1, copper foil loading of 1 g / cm 3 The counter electrode is a metal sodium sheet and the electrolyte is 1 mol / L NaPF 6 in diglyme, the diaphragm is a glass fiber diaphragm, and the assemblies are CR2023 button batteries for testing. The test voltage range is 0~2.5V, the current density is 0.1C~3C, and the charge and discharge rate of the first cycle coulomb efficiency is 0.1C.
[0023] The test results of the hard carbon material prepared in this example are as follows: Figure 1 This is the SEM image of hard carbon material. It can be seen that the final material has a lamellar structure and no obvious microscopic features. This is because the formation and composition of coal are relatively complex and there is no obvious crystal structure. Figure 2 This is the BET adsorption diagram of hard carbon materials. By changing different preparation conditions, it is found that large specific surface area has more surface defects. Although it can provide more sites, it will cause dead sodium phenomenon, making it impossible for sodium ions to escape after embedding, and unable to participate in subsequent reactions, resulting in a decrease in the first cycle coulomb efficiency and subsequent capacity. Figure 3 This is the XRD diagram of the hard carbon material. The material shows the characteristics of hard carbon, and there is no obvious impurity peak, especially the silica peak. Figure 4 This is the TEM image of hard carbon material, which shows the obvious long-range disorder and short-range order characteristics of hard carbon. The crystal plane interlayer spacing is 0.381nm, which is much larger than the 0.335nm of graphite, which is conducive to the embedding and extraction of sodium ions. Figure 6 This is the first cycle charge and discharge curve of the hard carbon material, reaching a charge specific capacity of 287mAh / g and a first cycle coulombic efficiency of 82.5%. Figure 7 , 8 These are the rate performance diagram and long cycle performance diagram of the hard carbon material. It can be seen that it has stable high-rate performance and excellent long-cycle stability. After 1800 charge and discharge cycles, the capacity remains above 80%.
[0024] The present invention can obtain similar material properties by changing different calcination temperatures (1000°C, 1200°C and 1450°C). Even if the temperature is directly increased to 1300°C without gradient heating, the electrochemical properties of the obtained material are not significantly reduced. Example
[0025] The difference between this embodiment and embodiment 1 is that the amount of zinc phosphate tetrahydrate added in step (3) is 0.5 g.
[0026] The rest of the preparation method and electrochemical performance test were consistent with those in Example 1. Example
[0027] The difference between this embodiment and embodiment 1 is that the amount of zinc phosphate tetrahydrate added in step (3) is 1.5 g.
[0028] The rest of the preparation method and electrochemical performance are consistent with those in Example 1. Example
[0029] The difference between this embodiment and embodiment 1 is that the amount of zinc phosphate tetrahydrate added in step (3) is 2 g.
[0030] The rest of the preparation method and electrochemical performance are consistent with those in Example 1.
[0031] Figure 5 This is a Raman spectrum of the coal-based hard carbon material prepared in Examples 1 to 4 of the present invention, wherein the ID / IG ratio reflects the degree of graphitization of the material. As the degree of graphitization increases, the interlayer spacing of the carbon material decreases, the characteristics of the hard carbon decrease, and the sodium storage performance decreases.
[0032] Comparative Example 1 The difference between this comparative example and Example 1 is that zinc phosphate tetrahydrate is not added in step (3).
[0033] The rest of the preparation method and electrochemical performance test were consistent with those in Example 1.
[0034] Fig. 9 , 10 The XRD diagram and the first charge and discharge curve of Comparative Example 1 also show the characteristics of hard carbon, but the capacity is limited.
[0035] Comparative Example 2 The difference between this comparative example and comparative example 1 is that the amount of anhydrous sodium carbonate added in step (3) is 1.33 g.
[0036] The rest of the preparation method and electrochemical performance are consistent with those in Example 1.
[0037] Comparative Example 3 The difference between this comparative example and comparative example 1 is that the amount of anhydrous sodium carbonate added in step (3) is 2 g.
[0038] The rest of the preparation method and electrochemical performance are consistent with those in Example 1.
[0039] Comparative Example 4 The difference between this comparative example and comparative example 1 is that the amount of anhydrous sodium carbonate added in step (3) is 4 g.
[0040] The rest of the preparation method and electrochemical performance are consistent with those in Example 1.
[0041] Comparative Example 5 The difference between this comparative example and comparative example 1 is that no acid washing is used in step (2), and no anhydrous sodium carbonate is added in step (3).
[0042] The rest of the preparation method and electrochemical performance are consistent with those in Example 1.
[0043] Comparative Example 6 The difference between this comparative example and comparative example 1 is that in step (2), after pickling with 2 mol / L hydrochloric acid for 12 h, pickling with 5% HF for 12 h is performed, and no anhydrous sodium carbonate is added.
[0044] The rest of the preparation method and electrochemical performance are consistent with those in Example 1.
[0045] Comparative Example 7 The difference between this comparative example and comparative example 5 is that the raw material lignite is replaced with sea anthracite.
[0046] The rest of the preparation method and electrochemical performance are consistent with those in Example 1.
[0047] The test results of the sodium ion half-cell prepared in the above example are shown in Table 1.
[0048]
[0049] As can be seen from the table above, the capacity of Comparative Example 5 without acid washing is very small, with a charge capacity of only 184 mAh / g, and compared with anthracite, its capacity is somewhat different from anthracite. After secondary acid washing with HF, the capacity of Comparative Example 6 reaches 238 mAh / g, which is a certain improvement, but HF is highly corrosive and causes serious environmental pollution, which is not conducive to large-scale production and application.
[0050] Comparative Examples 1 to 4 are samples that were pickled with hydrochloric acid and then added with a green impurity remover and pore-forming agent anhydrous sodium carbonate for impurity removal and activation. Among the four gradients, the optimal condition was obtained with an addition amount of 10% of Comparative Example 1, so that the capacity can reach a charge specific capacity of 268mAh / g, and the first-cycle coulomb efficiency is increased to 82.2%, which is a significant improvement. Comparative Examples 1 to 4 show that the addition of sodium carbonate significantly improves the performance of hard carbon materials in terms of capacity and first-cycle coulomb efficiency, and that the amount of sodium carbonate added also has a certain effect on the material in terms of activation and impurity removal. The purpose of sodium carbonate is to react with silicon dioxide in blue charcoal as an impurity remover to remove silicon therein; secondly, as an activator, it provides alkaline conditions at high temperature to activate and form pores for the material, providing more active sites for the embedding and removal of sodium ions in the material.
[0051] On this basis, zinc phosphate is added as a dopant to obtain a phosphorus-zinc dual-doped high electrochemical performance modified material. It can be seen from the data of the above Examples 1 to 4 that the present invention uses blue carbon as a raw material to prepare hard carbon, and improves the material microstructure by regulating the process parameters to improve the electrochemical performance of the material, thereby obtaining a blue carbon-based sodium ion battery negative electrode material with high capacity, high rate and long life. Among them, the first-cycle coulomb efficiency exceeds 80%, and the capacity is also significantly improved. Comparative Example 1 can achieve a charging capacity of 287 mAh / g, and the first-cycle coulomb efficiency reaches 82.5%; at the same time, the process flow of this material is simple, the cost of raw materials is low, and the pollution is small, and it has the potential for industrialization.
[0052] It should be noted that the above embodiments do not limit the present invention in any form, and the method of the present invention is only a preferred implementation scheme, and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a blue charcoal-based hard carbon material, characterized in that The following steps are involved: (1) crushing and sieving the semi-coke to obtain semi-coke fine powder; (2) The semi-coke fine powder is acid-washed to remove impurities, then washed with water until neutral, and dried to obtain acid-washed semi-coke; (3) Evenly mixing the acid-washed semi-coke with sodium carbonate and zinc phosphate, wherein the mass ratio of semi-coke, sodium carbonate and zinc phosphate is 10:(0.3-2):(0.3-2); (4) The blend obtained in step (3) is calcined at 1000-1500° C. under an inert atmosphere to obtain a blue charcoal-based hard carbon material.
2. The method for preparing the blue charcoal-based hard carbon material according to claim 1, characterized in that: In step (1), the semi-coke is crushed and passed through a 200-mesh sieve to obtain semi-coke fine powder.
3. The method for preparing the blue charcoal-based hard carbon material according to claim 1, characterized in that: In step (2), pickling uses one or more mixed acids selected from hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, acetic acid, propionic acid, and ethylenediaminetetraacetic acid, and the acid concentration is 0.5-6 mol / L.
4. The method for preparing the blue charcoal-based hard carbon material according to claim 1, characterized in that: In step (3), the mass ratio of blue carbon, sodium carbonate and zinc phosphate is 10: (0.5-1.5): (0.5-1.5).
5. The method for preparing the blue charcoal-based hard carbon material according to claim 1, characterized in that: In step (3), the blending is carried out by ball milling, mechanical stirring or rotary stirring.
6. The method for preparing the blue charcoal-based hard carbon material according to claim 1, characterized in that: In step (4), the inert atmosphere protective gas is a mixture of one or more of nitrogen, argon and carbon dioxide.
7. The method for preparing the blue charcoal-based hard carbon material according to claim 1, characterized in that: In step (4), the calcination is carried out in stages, room temperature - (550-650°C) - (800-950°C) - (1000-1500°C), and each stage is kept warm for 20 minutes to 2 hours.
8. The method for preparing the blue charcoal-based hard carbon material according to claim 1, characterized in that: In step (4), the calcined blue charcoal-based hard carbon material is subjected to acid washing and drying treatment.
9. The blue charcoal-based hard carbon material obtained by the preparation method according to claim 1.
10. Use of the blue charcoal-based hard carbon material according to claim 9 in negative electrode materials for sodium ion batteries.
Citation Information
Patent Citations
A nitrogen-doped coal-based hard carbon material, preparation method and application thereof, and secondary battery
CN116443850B
Method for flexibly regulating and controlling hard carbon negative electrode of lignite-based power type / capacity type sodium-ion battery and application of lignite-based power type / capacity type sodium-ion battery
CN116654893A
A coal-based hard carbon negative electrode material for sodium ion battery and preparation method thereof
CN117894982B
Coal-based hard carbon negative electrode sodium storage material as well as preparation method and application thereof
CN119176544A